Protective effect of antirheumatic drugs on dementia in rheumatoid arthritis patients. Issue 4 (9th November 2017) - Judge, Andy; Garriga, Cesar; Arden, Nigel K.; Lovestone, Simon; Prieto‐Alhambra, Dani; Cooper, Cyrus; Edwards, Christopher J.
Abstract: Introduction: Rheumatoid arthritis is a systemic inflammatory disease, and classical disease‐modifying antirheumatic drugs (cDMARDs) have proven efficacy. It is unknown what impact cDMARDs might have on dementia as an outcome. Methods: Incident diagnoses of rheumatoid arthritis in persons over 18 years from 1995 to 2011 were identified from the UK Clinical Practice Research Datalink. There were 3876 cDMARD users and were propensity score matched to 1938 nonusers, on a wide range of confounders. Impact on dementia was assessed using survival models. Results: cDMARD users were at reduced risk of dementia (hazard ratio: 0.60; 95% confidence interval: 0.42–0.85). The effect was strongest in methotrexate users (hazard ratio: 0.52; 95% confidence interval; 0.34–0.82). Discussion: The strong effect of cDMARD use on halving of dementia risk requires replication in a trial and may provide an important therapeutic pharmacological treatment.